Teachers' beliefs on conflict and conflict resolution - Oksana Obraztsova (University of Aberdeen, School of Education, 2018)
Conflict is a natural part of life and a part of school life, too. Teachers might be involved in conflicts with students, their parents and colleagues. The point is not to avoid conflicts or to resolve them with administrative tools, but to handle them productively. Conflict management strategies are important in maintaining human relationships, positive classroom environment and school climate. To manage conflicts efficiently, teachers need knowledge and understanding of nature of conflict, special skills and methods of conflict resolution in practice, as well as readiness to conflict management. To analyse teachers' beliefs on conflict nature and conflict transformation the empirical study using mixed methods approach was organized. Participants were secondary school teachers and university teachers from Arkhangelsk and Severodvinsk (n=133). Methods used were interview of experts and questionnaire for teachers with close-ended questions and scaled questions constructed in the format of a typical five-level Likert items. The teachers realize the basic nature of conflict and humans' behaviour in it, but their beliefs are rather ambivalent. There are some differences in the beliefs of school teachers and university teachers; both groups of teachers chose the compromise as prevailing conflict strategy but recognize the lack of knowledge and skills in the field of practical conflict resolution. The study hasn't found out significant differences in teachers' beliefs associated with gender, age and teaching speciality.